(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This article explores the phenomenon of transient bimodality in in- novation diffusion and its implications for the extended Bass model. By incorporating population heterogeneity and random parameters, the ex- tended Bass model predicts the occurrence of multimodal life cycle pat- terns in addition to the conventional unimodal pattern. Through analyt- ical investigations and case studies, we analyze the dynamics of transient bimodality and its implications for understanding and managing innova- tion diffusion. Our findings shed light on the complex nature of diffusion processes and offer valuable insights for researchers and practitioners in the field.